Analisis Kepuasan Pengguna Pada Learning Management System Classes Menggunakan Metode End User Computing Satisfaction - Dwi Yana Wijaya; Ahyar Muawwal; Renny (STMIK KHARISMA Makassar, 2021)
Classes is an Learning Management System service to assist teachers in delivering material and supervising student learning. The study was conducted to determine the quality of service by analyzing user satisfaction in using the website class. In this study, the method used is the End User Computing Satisfaction (EUCS) method to analyze user satisfaction by comparing reality and expectations. The EUCS method measures user satisfaction based on five variables, namely content, accuracy, format, timeliness and ease of use. The sampling is done by non-probability sampling technique The selection is done randomly. Based on the results of this study based on the results of the R test, it is known that the determination of 0.944 means that X which consists of content, accuracy, format, ease of use and timelines simultaneously gives an effect on Y of 0.880 or 88.0%. This means that from 55 respondents, 48 ​​respondents were satisfied with the website class. Based on the T test there are 2 variables that have no effect on Y, namely content and format and there are 3 X variables that affect Y. In the content and format variables respondents are not satisfied while on accuracy, timeliness and ease of use they are satisfied with these 3 variables.